Synthesis and Activity Evaluation of Gemcitabine Prodrugs with 4-(Boronic acid) benzoylamide Structure - Jiang, Chunfeng; Wang, Xianrui; An, Changwei; Jiang, Jiaqi; Su, Tongjia; Liu, Meiwei; Xu, Xiaobo; Zeng, Qinglin (Synlett, 2025)
A convenient approach was developed for the syntheses of amide derivatives and novel gemcitabine prodrugs with 4-(boronic acid) benzoylamide structure. The amide compounds containing the phenylboronic acid structure were synthesized by a one-step reaction strategy using o-toluidine and 4-boronobenzoic acid as starting materials. Also, the pure product was quickly obtained through acid–base post-treatment. Moreover, the prodrugs of gemcitabine containing phenylboronic acid structure were rapidly synthesized by the microchannel continuous flow technology. Three of all the obtained targets were subjected to the antiproliferative activity test.
Keywords: Gemcitabine prodrug; 4-(Boronic acid) benzoylamide compounds; Amination reaction; Flow chemistry; Antitumor activity assay